ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PERSAMAAN KUADRAT - Sihafudin Sihafudin; Tuhfatul Janan (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2023)
The observation of this study aims to find out some of the errors and the level of understanding of students in working on several types of quadratic equation problem models, because these errors must be corrected so that it is easier to solve problems in the future. By using a qualitative descriptive method, the researcher hopes to help reduce mistakes made by students when working on practice questions and exams. The researcher used subjects from class IX students of SMPI Nurul Hidayah for the 2022/2023 academic year. Data collection techniques in this observation were UH (daily tests) and per-student interviews. The conclusion from this study there are 5 types of subject errors, namely errors when determining the roots of a quadratic equation, writing set brackets, writing mathematical notation, determining the values of ð‘Ž, ð‘, and ð‘ in general equations, and writing the value of the product of negative numbers.Keywords: error analysis, quadratic equation